Issues of Entering New Market and Ways to Overcome the Issues Company: F&N Holdings Berhad - Jun, Ooi Ee; Kee, Daisy Mui Hung; Wen, Tan Xiang; Chen, Koay Xiem; Qi, Ma Jia; AlDeehani, Faisal (AIBPM Publisher, 2019)
Solutions Resolve for Problem Encountered of Entering New Market in Fraser & Neave Holdings Bhd (F&NHB) F&NHB is among the oldest and most successful businesses in Singapore and Malaysia with core expertise and leadership in the food, beverage and other sectors. 135 years ago, two visionaries who are John Fraser and David Chalmers Neave formed The Singapore and Straits Aerated Water Company to produce carbonated soft drinks. This company eventually became one of the region’s food and beverage giants which is Fraser & Neave (F&N). Now, this company had been listed on Bursa Malaysia’s main board. F&NHB has an annual turnover in excess of RM 4 billion from its core business in the manufacture, sale and marketing of beverages and dairy products. In the present work, there are a problem encountered for entering new market of F&NHB according to our research. In fact, entering new market is a big challenge for every company because it represents the company must expand its business scope to make more profits. Before entering new market, F&NHB must determine the problems which will be faced in the future through analysing the political environment, economic environment, social and technology environment. Therefore, information is gathered to make the best decision for the market entry. Subsequently, solutions will be sought out and discussed to solve the issues which occurred in following new market through investigation. We will collect the data needed by referring the company website and other websites then analyse data to make the assignment completed.